Influence of cutting parameters on chatter and tool wear during end milling of stainless steel conducted on VMC - Amin, A. K. M. Nurul; Imran, M.; Arif, M. (IIUM Press, 2002)
Stainless steels are a group of difficult to machine work materials. The difficulty in machining stainless steels is manifested in high contact length and stresses, formation of serrated chips and development of chatter resulting in high tool wear rates and poor machined surface finish. The paper focuses on the performance of TiN coated-carbide inserts in machining stainless steel specimens in end milling operation performed on vertical machining centre (VMC). The performance of the tool is evaluated from the point of view of its wear intensity, mechanism of failure and generation and effect of chatter on tool wear and vice versa. The investigations were aimed at determining the effect of cutting parameters, specifically cutting speed, feed and depth of cut, on chatter amplitude, tool wear rate, mechanism of tool wear and using these data and machined surface roughness values from previous work to come up with recommended values of cutting parameters for semi-finish and finish end milling operation of stainless steel work materials. For recording vibration signals a dual channel portable signal analyzers was used and the signals were analyzed using Pulse Multi-analyzer version 4.2 software. Tool wear was measured using an optical microscope with digital readout capabilities along 3 axes. The tool wear mechanisms were studied under a scanning electron microscope (SEM). Results of the investigation show that acceleration amplitudes generally increase with cutting speed and the magnitude of tool flank wears. It has been also found that an increase in feed and depth of cut leads to higher acceleration amplitudes. The most common wear mechanisms observed during machining of stainless steel are attrition, micro and macro chipping of the tool at lower cutting speeds, and diffusion and mechanical failures due to intensive chatter at higher speeds. It has been also established that stable cutting speeds with relatively low tool wear intensity and satisfactory machined surface finish can be achieved through proper selection of cutting parameters. A table of recommended cutting conditions has been developed for almost chatter free machining with low tool wear intensity and satisfactory surface finish.